1989
DOI: 10.1152/ajpcell.1989.256.2.c358
|View full text |Cite
|
Sign up to set email alerts
|

Ca-induced Ca release in malignant hyperthermia-susceptible pig skeletal muscle

Abstract: To provide information regarding the cause of the muscle rigidity in malignant hyperthermia-susceptible (MHS) pigs, the Ca-induced Ca-release mechanism of the sarcoplasmic reticulum (SR), the Ca uptake by the SR, and the Ca-activated tension production of the contractile system were examined in skinned skeletal muscle fibers from MHS and normal pigs. In muscles of MHS pigs, the rate of Ca-induced Ca release was significantly higher than in normal muscle. The potentiation effect on Ca-induced Ca release by halo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 13 publications
3
41
1
Order By: Relevance
“…In agreement with previous reports (7,12,13,45,46), we found that the extent of dantrolene inhibition of DP4-induced RyR1 channel activation, as determined by both [ 3 H]ryanodine binding and SR Ca 2ϩ release, varies with the temperature, i.e. significant inhibition was observed at 37°C, with only negligible inhibition at 22°C.…”
Section: Table III Inhibition Of Sr Ca 2ϩ Release By Dantrolene: Effesupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous reports (7,12,13,45,46), we found that the extent of dantrolene inhibition of DP4-induced RyR1 channel activation, as determined by both [ 3 H]ryanodine binding and SR Ca 2ϩ release, varies with the temperature, i.e. significant inhibition was observed at 37°C, with only negligible inhibition at 22°C.…”
Section: Table III Inhibition Of Sr Ca 2ϩ Release By Dantrolene: Effesupporting
confidence: 93%
“…CaM alone (1 M) increased the specific activity of [ 3 H]ryanodine binding to the SR at 22°C, but dantrolene was now able to significantly suppress radioligand binding (ϳ35%) (Table II). When we carried out the same type of experiments at 37°C, dantrolene produced equivalently significant inhibition of [ 3 H]ryanodine binding (ϳ59%) in the presence or absence of CaM, in agreement with previous reports (7,12,13,45). These results suggest that higher temperature and CaM have similar effects on the extent of dantrolene inhibition of DP4-induced activation of RyR Ca 2ϩ channels.…”
Section: Inhibition Of Skeletal Muscle Sr Ryanodine Binding and Ca 2ϩsupporting
confidence: 91%
“…As a positive control, we also introduced an Arg615Cys (R615C) mutation, which is known as the causal mutation in porcine stress syndrome, an animal model of MH (24). Indeed, significant acceleration of the CICR has been detected in muscle samples from MH pigs (25). RyR1 cDNAs carrying one of these mutations were coexpressed in CHO cells with EGFP using a bidirectional expression vector (26).…”
Section: Expression and Functional Analysis Of The Two Novel Ryr1 Mutmentioning
confidence: 99%
“…Indeed the patient took cefpodoxime proxetil and indomethacin but these agents have not been documented to cause malignant hyperthermia or neuroleptic malignant syndrome. In patients with malignant hyperthermia, the calcium release rate in the sarcoplasmic reticulum was demonstrated to be abnormally enhanced by the stimulation of calcium, with the use of skinned fiber preparations (2,5). Therefore the possibility was tested by this method using the present patient's muscle specimen.…”
Section: Discussionmentioning
confidence: 97%
“…Using this, the calcium release rate in the sarcoplasmic reticulum was measured (2,5). The calcium release rate was measured with application of5 different concentrations of calcium: 0, 0.3, 1.0, 3.0 and 10 \\M.…”
Section: Blood Purificationmentioning
confidence: 99%